Comparative analysis of thermal and acoustic performance of composites made from wood fibres, recycled rubber and ABS - Georgescu, S V; Cosereanu, C (IOP Publishing, 2018)
The paper investigates the thermal and acoustic properties of composites made from wood fibres (WF) and recycled rubber (R) crumbs and acrylonitrile butadiene styrene (ABS) shavings resulted in the particleboards' edge banding. Panels with a target density of 300 kg/m(3) were manufactured for testing the thermal conductivity coefficient and sound absorption coefficient. Mixed panels WF: ABS, R: ABS with participation rates (in %) of 10: 90, 20: 80, 30: 70; 40: 60; 50: 50 and WF: R: ABS with participation rates (in %) of 5: 5: 90, 10: 10: 80, 15: 15: 70; 20: 20: 60; 25: 25: 50 were investigated in this paper. The experiment simulated the indoor and outdoor temperature conditions for the winter and summer seasons, namely 20 degrees C for indoor and -10 degrees C to 35 degrees C for the outdoor temperatures. The results show that, with the increase of ABS share, the thermal performance of the panel increases. The presence of WF in the composition has a good influence on the thermal performance of the panels, whilst the presence of rubber brings a better acoustic performance of the composites. The analysis of the results show that the thermal conductivity coefficient (lambda) experimentally determined depends on the outdoor temperature and recorded the best value for the composite WF-ABS (0.0434 Wm(-1)K(-1)) followed by WF-R-ABS (0.0460 Wm(-1)K(-1)) and R-ABS (0.0477 Wm(-1)K(-1)). Maximum values were recorded for R-ABS structure at a temperature of 35 degrees C (0.0573 Wm(-1)K(-1)), but this structure recorded the best sound absorption coefficient (0.87).
Keywords: MECHANICAL-PROPERTIES; DENSITY POLYETHYLENE; TIRE RUBBER; BLENDS